2007
DOI: 10.1161/01.atv.0000258416.47953.9a
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Training Restores Coronary Arteriolar Dilation to NOS Activation Distal to Coronary Artery Occlusion

Abstract: Objective-Exercise training has been shown to restore vasodilation to nitric oxide synthase (NOS) activation in arterioles distal to coronary artery occlusion. Because reactive oxygen species are generated during NOS uncoupling and the production of vasodilator H 2 O 2 is increased during exercise in patients with coronary disease, we proposed that H 2 O 2 may contribute to the restoration of vasodilation in porcine coronary occlusion model. Methods and Results-Left circumflex (LCX) coronary artery of miniatur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 59 publications
2
20
1
Order By: Relevance
“…However, this modified catalase caused loss of basal tone of coronary arterioles, and the vasomotor activity could not be further studied. Nevertheless, using an effective concentration of unmodified catalase, 29,30 we found that the adverse effect of CRP remained (Online Figure II), suggesting nominal contribution of hydrogen peroxide in mediating the CRP effect in our preparation.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, this modified catalase caused loss of basal tone of coronary arterioles, and the vasomotor activity could not be further studied. Nevertheless, using an effective concentration of unmodified catalase, 29,30 we found that the adverse effect of CRP remained (Online Figure II), suggesting nominal contribution of hydrogen peroxide in mediating the CRP effect in our preparation.…”
Section: Discussionmentioning
confidence: 81%
“…The roles of LOX-1 and CD32 in mediating the CRP effect were examined in a separate group of vessels by determining dilation to serotonin before and after coadministration of CRP with an anti-LOX-1 antibody (5 µg/mL; Abcam) 25 or an anti-CD32 antibody (5 µg/mL; Santa Cruz Biotechnology). 26,27 κ-Carrageenan (125 µg/mL), a LOX-1 antagonist, 25,28 and catalase (1000 U/mL), 29,30 the hydrogen peroxide scavenger, were administered to determine the role of LOX-1 and hydrogen peroxide, respectively, in the observed CRP effect. In another cohort of vessels, vasodilation to arachidonic acid (10 µmol/L), 10 an endothelium-dependent PGI 2 -mediated agonist, was examined before and after incubation with PGI 2 synthase inhibitor trans-2-phenyl cyclopropylamine (TPC; 100 µmol/L) 10 or after 60-minute intraluminal incubation with recombinant CRP (7 µg/mL) in the absence or presence of an anti-LOX-1 antibody (5 µg/ mL), TPC plus an anti-LOX-1 antibody, or an anti-CD32 antibody (5 µg/mL).…”
Section: Functional Assessment Of Isolated Coronary Arteriolesmentioning
confidence: 99%
“…Animal models have also found that regular aerobic exercise restore arterial function in the microcirculation in an H 2 O 2 -dependent fashion. In a porcine model of coronary artery disease, regular exercise restored microvessel dilatory function via H 2 O 2 -mediated dilation [29]. Huang et al [30] showed impaired microvessel FMD following transient high intraluminal pressure (140 mmHg) was restored following administration of exogenous SOD, also suggesting a role H 2 O 2 -mediated FMD.…”
Section: Discussionmentioning
confidence: 98%
“…Since H 2 O 2 and the CYP enzyme metabolites EETs have been suggested to be involved in the EDHF-induced vasodilation in some vascular beds, 9 we tested this possibility by pretreating the vessels with the effective concentration of H 2 O 2 scavenger catalase (1000 U/mL) 40,41 and the CYP2C9 enzyme inhibitor sulfaphenazole (10 lM), 42 respectively. The role of gap junctions in histamine-induced responses was tested by the gap junction inhibitor carbenoxolone (100 lM).…”
Section: Chemical Nature Of Edhf and The Role Of Gap Junctionsmentioning
confidence: 99%